1995
DOI: 10.1029/95gl00605
|View full text |Cite
|
Sign up to set email alerts
|

Ozone trends deduced from combined Nimbus 7 SBUV and NOAA 11 SBUV/2 data

Abstract: The long‐term time series of global ozone from the Nimbus‐7 SBUV (Nov. 1978–June 1990) are extended through June 1994 by using measurements from the NOAA‐11 SBUV/2. The data sets are merged based upon comparisons during the 18‐month overlap period in which both instruments were operational. During this period, the average offset between the two time series is less than 2% in total ozone, and less than 6% in Umkehr layers 1–10. A linear‐regression trend model is applied to the extended time series to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 7 publications
(9 reference statements)
2
31
0
Order By: Relevance
“…There are seasonal differences in upper stratospheric ozone trends. Trends are largest in winter and smallest in summer (Hood et al, 1993;Hollandsworth et al, 1995b). Recent estimates from SBUV version 8 data for the 1979-97 period over northern mid-latitudes at 2-3 hPa show a decline of 5.7±2.8% per decade in winter and 3.1±1.5% per decade in summer (Rosenfield et al, 2005).…”
Section: Yearmentioning
confidence: 97%
“…There are seasonal differences in upper stratospheric ozone trends. Trends are largest in winter and smallest in summer (Hood et al, 1993;Hollandsworth et al, 1995b). Recent estimates from SBUV version 8 data for the 1979-97 period over northern mid-latitudes at 2-3 hPa show a decline of 5.7±2.8% per decade in winter and 3.1±1.5% per decade in summer (Rosenfield et al, 2005).…”
Section: Yearmentioning
confidence: 97%
“…The monthly anomalies, the difference between the individual monthly means and their 20-year average, are plotted for the region between 30 • N and 60 • N in Fig. 4 for both ozone schemes and also for the total ozone data from the TOMS (McPeters et al 1996) and SBUV (Hollandsworth et al 1995). The anomalies have been smoothed by a 24-month running mean to average over both the annual cycle and the QBO, as in the earlier studies of Solomon et al (1996Solomon et al ( , 1998.…”
Section: Interannual Variations and Trends Of Ozone (A) Perpetual Expmentioning
confidence: 99%
“…Hollandsworth et al (1995) found that the seasonal trends computed from the SBUV(/2) record varied by more than 0.2% per year when the length of the data set was extended from 11.5 years to 12.5 years.…”
mentioning
confidence: 99%
“…We use the 15-year combined record of ozone profile measurements from the Nimbus 7 (N7) SBUV and NOAA 11 (Nll) SBUV/2 instruments employed by Hollandsworth et al (1995) and the linear regression statistical model described in Hood et al (1993) to examine trend differences due to: varying the time interval, selecting zonal average data as compared to station data, and including QBO and ll-year solar cycle terms.…”
mentioning
confidence: 99%